Pemberdayaan Purna Pekerja Migran Indonesia secara Partisipatif untuk Mengurangi Pengangguran di Desa Karangpatihan Kabupaten Ponorogo - Ruth Agnesia Sembiring; Mayang Agustin (Universitas Medan Area, 2023)
This qualitative descriptive research focuses on the participative empowerment of Indonesian former migrant worker to reduce unemployment in Karangpatihan village of Balong sub district in Ponorogo regency of East Java. In this study, people’s participation in development is used as the tool of analysis. This research was conducted in five stages: identification of problems, program formulation, program execution, program evaluation, and enjoying the program’s outcome. The data was harvested through observations, interviews, and documentations. This study finds that passive participants were found in the initial phase of the program due to their pessimism to the event’s outcome. People’s participation in this program increased after many of the past participants were successful of becoming independent individuals; 250 people out of 413 are having and running their own business. Based on the five indicators of empowerment success’, this study finds that the empowerment of former migrant workers can reduce the number of unemployed people, both former migrant workers and non-migrant workers. The program also helps former migrant workers with their business, increases their awareness to poor families around them, strengthens their independency, and enhances their ability to fulfill their daily needs.